THE IMPLEMENTASI KEBIJAKAN PUBLIK DALAM PERCEPATAN PENDAFTARAN TANAH SISTEMATIS LENGKAP PADA KANTOR BADAN PERTANAHAN NASIONAL KABUPATEN OGAN ILIR (THE PUBLIC POLICY IMPLEMENTATION IN ACCELERATING A COMPREHENSIVE SYSTEMATIC LAND REGISTRATION AT OGAN ILIR RE - Hardiyansyah - - (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2019)
The National Land Agency (NLA) of Ogan Ilir Regency in 2018 targeted 5400 land certificates issued through the implementation of a complete systematic land registration acceleration. But the reality shows that BPS is only able to issue 27, 39% or 1951 certificates. PTSL policy is launched to anticipate that there are still many land that has not been certified in various regions in Indonesia, including in the Ogan Ilir Regency area. Through descriptive qualitative research methods with in-depth interviews with selected informants and field observations, as well as triangulation analysis methods, the results of the research show that the implementation of PTSL acceleration policies in general has been in accordance with standard operating procedures (SOP) but budget support is not maximal. that is still small and the quality is still low, people are less concerned and still reluctant to register their land for reasons that are slow, long and expensive and the level of difficulties that are different in the process of measuring land / land. The findings of this study recommend to the National Land Agency that the implementation of PTSL policies will be able to run optimally if it is supported by an adequate budget, sufficient and quality apparatus and quality services. Keywords: policy implementation, comprehensive systematic land registration, BPN, Ogan Ilir